2020
DOI: 10.1186/s12936-020-03221-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Plasmodium vivax populations in border areas of the Greater Mekong sub-region during malaria elimination

Abstract: Background: Countries within the Greater Mekong Sub-region (GMS) of Southeast Asia have committed to eliminating malaria by 2030. Although the malaria situation has greatly improved, malaria transmission remains at international border regions. In some areas, Plasmodium vivax has become the predominant parasite. To gain a better understanding of transmission dynamics, knowledge on the changes of P. vivax populations after the scale-up of control interventions will guide more effective targeted control efforts.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 78 publications
1
10
1
Order By: Relevance
“…The proportion of vivax malaria cases in Yingjiang County increased from 2013 to 2019 and no falciparum malaria cases were reported in 2019, indicating that P. vivax was the predominant species on the Myanmar side and the rate of P. falciparum infection in Myanmar was very low because more than 95% of the imported cases were from Myanmar. This change was similar to that in other countries in the Greater Mekong sub-region 28 , 29 . The epidemiology of vivax malaria in this region is highly heterogeneous and P. vivax has become a major challenge to malaria elimination in this region 30 , 31 .…”
Section: Discussionsupporting
confidence: 87%
“…The proportion of vivax malaria cases in Yingjiang County increased from 2013 to 2019 and no falciparum malaria cases were reported in 2019, indicating that P. vivax was the predominant species on the Myanmar side and the rate of P. falciparum infection in Myanmar was very low because more than 95% of the imported cases were from Myanmar. This change was similar to that in other countries in the Greater Mekong sub-region 28 , 29 . The epidemiology of vivax malaria in this region is highly heterogeneous and P. vivax has become a major challenge to malaria elimination in this region 30 , 31 .…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have found PvDBP-II under a strong selection. The high rates of non-synonymous to synonymous mutations reflected a positive selection promoting greater polymorphism, which may allow the evasion of host immune selection independently of the geographical distribution ( Li et al, 2020 ). In this study, the rate of non-synonymous to synonymous mutations indicated that the PvDBP-II of CMB isolates was also under positive selection.…”
Section: Discussionmentioning
confidence: 99%
“…P. vivax has become the most dominant parasite in the GMS region. Better understanding of transmission dynamics and population structure is essential to develop appropriate interventions for malaria elimination ( Li et al, 2020 ). Myanmar border malaria is a major source of disease transmission and infection in the CMB in Yunnan Province.…”
Section: Discussionmentioning
confidence: 99%
“…Although malaria incidences have significantly declined in the central part of Myanmar in the last decade, migration from endemic areas or international border areas such as the Myanmar-China and Myanmar-Thailand borders has been increasing in recent years due to political instability and job recruiting. Large P. vivax reservoirs, including asymptomatic individuals, still maintain genetic diversity and transmission in the border areas with considerable spatial and temporal differentiations [ 6 , 26 , 27 ]. Further studies on the influx of P. vivax from other endemic areas or boarder areas and its contribution to the population diversity of P. vivax in Mandalay areas are also necessary to understand the causes of the increase in genetic diversity of the P. vivax population in the studied areas, and to provide guidelines for effective control measures.…”
Section: Discussionmentioning
confidence: 99%